Distinct ionospheric long-term trends in Antarctica due to the Weddell Sea Anomaly - M. Canales; T. Duran; M. Bravo; A. Zalizovski; A. Zalizovski; A. Zalizovski; A. Foppiano (Annales Geophysicae)
The Weddell Sea Anomaly (WSA), a summer ionospheric anomaly over the eastern Antarctic Peninsula, was first observed in 1958 and is characterized by a nighttime peak in electron concentration instead of a the typical daytime peak. There are some works that examine long-term trends at ionospheric stations in the WSA region, but they do not do a seasonal and diurnal analysis that is vital for differentiating the periods of the anomaly. This study investigates the seasonal and diurnal variation in the long-term trend in the F2-layer critical frequency (foF2) at ionospheric stations located within the WSA region: Vernadsky (Argentine Island; 65.1° S, 64.2° W) and Port Stanley (51.6° S, 57.9° W), both with long-term foF2 data. Data from Vernadsky (1960–2023) and Port Stanley (1960–2019) were analyzed alongside data from Syowa (69.0° S; 39.6° E) and Mawson (67.6° S, 62.9° E), two stations outside the WSA influence. The analysis reveals distinct seasonal and diurnal trends. For Vernadsky, negative foF2 trends (−0.02 MHz yr−1) are observed during summer nights, coinciding with the WSA's presence. Port Stanley shows similar trends but with a secondary nighttime maximum. The WSA's influence on Vernadsky is more pronounced, with Port Stanley exhibiting a weaker mid-latitude summer evening anomaly. In contrast, Syowa and Mawson show different trends, with Syowa not having a clear trend pattern, and Mawson showing negative trends throughout the year. The study concludes that the WSA significantly affects Vernadsky and, to a lesser extent, Port Stanley. The findings highlight regional variations in ionospheric behavior and contribute to the ongoing discussion on global ionospheric trends, suggesting that local phenomena like the WSA can modulate these trends.